Modeling Adoption Behavior toward Islamic Microfinance: A Comparative Study Between Malaysia and Indonesia - Abidin, Nur Liyana Zainal; Suhartanto, Dwi; Burhany, Dian Imanina (Politeknik Negeri Bandung, 2024)
This study probes the focal factors influencing the intention of young SME leaders to adopt Islamic microfinance. The researchers merged the existing model together with new variables, such as the perception of financial benefits and the perception of financial cost along with awareness, religiosity, and knowledge behind TPB through attitude in order to construct the aid to amplify the predictive efficacy and examine its effects on young SME leaders’ willingness to adopt Islamic microfinance. The research questionnaire was distributed using Google Forms to young SME leaders in Malaysia and Indonesia with a total sample of 300 respondents. Data obtained were then analyzed using partial least squares (PLS) by employing SmartPLS. This study reveals that perceived behavioral control and subjective norms have a positive significant impact on young SME leaders’ intention to adopt Islamic microfinance. The findings underscore the importance of these two elements toward the intention, awareness, and religiosity toward the intention through attitude.